Augmented criminality: How people process in situ augmented reality crime information in relation to space/place. (September 2020) - Liao, Tony; Yang, Hocheol; Lee, Songyi; Xu, Kun; Bennett, Spencer McLain
Communication about crime and the places it occurs has been an important area of study for criminology, sociology, public policy, and media scholars. Where incidents used to be communicated through word of mouth, physical evidence, and news outlets, recent advances in crime tracking, mapping, and mobile media have dramatically changed how individuals are informed about crime. Many organizations have adopted mobile text alerts, and recent advances in augmented reality (AR) technologies have made it possible to overlay visuals about crime on top of users' physical surroundings. How people make sense of this visual, individualized, and location-specific crime information, however, is largely unknown and complicated by the fact that mobile technologies are challenging to study in situ, as people move through and experience urban place. Within the AR literature, while existing research has started to look at the ways that AR can affect people's experience of place, the precise ways that people perceive and integrate AR displays into their understanding of place are still largely unexplored. This empirical study reports findings from a project utilizing AR as an urban probe, where we took participants ( N = 57) around to places in a large metropolitan area in the United States and showed them visual AR crime information overlaid on the physical place where they were moving through. After seeing these urban probes, participants were asked what they noticed, remembered, and thought occurred in that place when shown AR crime information. The analysis draws on Lefebvre's (1991) spatial triad to explain how people read places through the lens of AR, and also how they extrapolate, speculate, and make associations from AR information. Based on these findings, this study discusses the implications for mobile media scholars and their understanding of visual place-based communication, as well as for designers and policymakers considering the use of AR to communicate crime information.